The Grand Tour and the North-South Axis of the Nineteenth Century Book Trade: The Pan-European Trade of Foreign-Language Editions and the Forces of Incorporation that Reshaped the Industry - Gabriele, Alberto (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2018)
While a rich scholarly production has mapped the tropes of travel literature and the changes in the forms of travel heading toward the ruins of past civilizations in Italy, Greece and the Ottoman Empire, less attention has been given to the coterminous geography of production and distribution of print culture along a North-South axis that accompanied these travelers at a time when the practice of issuing unauthorized cheap reprints in the continent fueled a rhetoric of stigmatization of foreign products, which went counter to the imagined open horizons and transformative experiences of travel on the Grand Tour. An extensive recensio (review and comparison) of title-pages of the editions of publishers in ten countries, as well as a perusal of the detailed records of the Leipzig Book Fair in the period 1800–1860, enable us to adopt a synchronic development of several interconnected practices and national markets. The article shall focus on three publishers, Loescher in Turin, Wilberg in Athens, and Weiss in Istanbul, who were all connected to the Leipzig industry, in order to explore several topics: the shifting allegiance to liberalism among publishers on the move, the importance of non-hegemonic languages in this trade, and the changing roles of publishers and booksellers under the impact of the forces of incorporation within the book industry.